Early symptoms of systemic lupus erythematosus (SLE) recalled by 339 SLE patients. (August 2018) - Leuchten, N; Milke, B; Winkler-Rohlfing, B; Daikh, D; Dörner, T; Johnson, S R; Aringer, M
Objective: The European League Against Rheumatism and the American College of Rheumatology jointly embarked on a new classification criteria for systemic lupus erythematosus (SLE) project. Its first phase involved generation of a broad set of items potentially useful for classification of SLE. This study was undertaken to add the patient perspective to an expert Delphi approach and an early patient cohort study. Methods: A national cross-sectional study was conducted. A self-report questionnaire was published in the "Schmetterling" (Butterfly), the quarterly journal of the German SLE patient association. Individuals with SLE were asked to anonymously complete the questionnaire, which asked for demographic details, organ manifestations, autoantibodies and symptoms. Results: A total of 339 completed questionnaires out of 2498 were returned, a response rate of 13.6%; 83.2% reported they were ANA positive and 81.7% reported joint, 66.1% skin and 33.0% renal involvement. For the time before and in the first year after their SLE diagnosis, the majority reported fatigue (89.4%), joint pain (86.7%), photosensitivity (79.4%) and myalgia (76.1%). Of interest, more than half of the patients reported fever as an early symptom (53.7%). Conclusion: For a Caucasian European SLE patient population, the overall characteristics suggest meaningful representation. While many symptoms were reported as expected, the high percentage of patients reporting fever and the significant number of patients with unexpected gastrointestinal complaints are of particular interest. These data add to the information on early SLE symptoms informing the development process of new SLE classification criteria.